2014
DOI: 10.1108/qaoa-08-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and dementia: an exploratory study of the views of audiologists

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:374558 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…LTC staff and hearing/vision clinicians may lack the skills and confidence to work with people with dementia, 3 , 25 or assume that people with dementia would not benefit from hearing/vision intervention. But systematic reviews identified benefits in terms of increased quality of life, improved communication, improved functional ability and reduced behavioural and psychological symptoms of dementia following hearing/vision interventions for people with dementia 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTC staff and hearing/vision clinicians may lack the skills and confidence to work with people with dementia, 3 , 25 or assume that people with dementia would not benefit from hearing/vision intervention. But systematic reviews identified benefits in terms of increased quality of life, improved communication, improved functional ability and reduced behavioural and psychological symptoms of dementia following hearing/vision interventions for people with dementia 9 .…”
Section: Discussionmentioning
confidence: 99%
“…LTC staff and hearing/vision clinicians may lack the skills and confidence to work with people with dementia, 3,25…”
Section: Multivariable Analysismentioning
confidence: 99%
“…If they are aware of hearing problems, carers may assume that hearing cannot be reliably assessed among PwD. Hearing care professionals may lack the confidence to work with PwD ( Wright et al 2014 ), or feel that PwD will not be able to use or benefit from hearing interventions. However, reliable hearing assessment is possible for most PwD, provided that assessment is adapted to the needs of PwD ( Bott et al 2019 ) and systematic reviews indicate that PwD do benefit from hearing intervention ( Dawes et al 2019b ; Mamo et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further research is needed in this area. Given that conservatively, one in five adult patients seen by audiologists will have dementia (Pichora-Fuller, Dupuis, Reed, & Lemke, 2013;Wright et al, 2014), audiologists need to be aware of the strengths and limitations of all diagnostic tests (behavioural and AEP) for adults with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the dearth of clinically driven research conducted with this population could be due to challenges with recruitment, namely obtaining consent, of participants with dementia (Looi et al, 2004). Despite this challenge, further research is required to support clinicians who provide hearing services to this population (Wright et al, 2014), as previous research indicates that hearing impairment results in additional communication consequences for adults living with dementia (Hopper & Hinton, 2012). One way to conceptualise the consequences of hearing impairment is by using a framework, such as the WHO's International Classification of Functioning, Disability and Health (ICF;WHO, 2001).…”
Section: The Need For This Researchmentioning
confidence: 99%